MEASUREMENT OF FINANCIAL PERFORMANCE IN ADOPTION OF THE ROGOTRUNNING VILLAGE BUDGET YEAR 2015 - 2018 - Dhayu Eka Septian; Setyo Liyundira, Fetri; Supartini, Supartini (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2020)
This study aims to determine the financial performance in the absorption of Rogotrunan Urban Budget and the 2015-2018 Budget Year period. This research includes quantitative descriptive research. The analytical method used in this study is the method of Shopping Growth Analysis and Shopping Variance Analysis. The results of this study indicate that the Financial Performance of Rogotrunan Urban Village in 2015-2018 can be considered Good because the absorption rate of the budget does not exceed the highest limit in absorbing the budget, in this case the absorption of the budget in Jogoyudan village refers to the Budget and Activity Plan, and allocating expenditure that is balanced and in accordance with the need is a very important thing in the preparation of the budget and in the absorption of the budget should refer to the Budget Work Plan is not permitted to set the standard prices that have been prepared so that the financial performance in the absorption of the budget can be considered good.